Gambaran Pemikiran Eksistensialisme Sartre Dalam Karakter Utama Komik One Piece Karya Oda Eichiro - Moh. Rizchald Walidain; Syihabuddin Syihabuddin (Peneliti.net, 2023)
This research discusses the existentialism views of Sartre in the main character of the comic One Piece by Oda Eichiro. Existentialism is a philosophical movement that focuses on the individual consciousness and freedom of choice of human beings. In this research, a qualitative descriptive research method is used to analyze the character structure of the main character in the One Piece series. This research includes an analysis of the background, motivation, personality, behavior, and dialogue of the character. The principles of Sartre's existentialism found in the main character of One Piece are subjectivity, responsibility, and freedom. This research shows that the main characters in the One Piece comic reflect Sartre's existentialism views through the actions and decisions he takes.